2020
DOI: 10.1038/s41589-020-00695-1
|View full text |Cite
|
Sign up to set email alerts
|

YY1 interacts with guanine quadruplexes to regulate DNA looping and gene expression

Abstract: Summary The DNA guanine quadruplexes (G4) play important roles in multiple cellular processes, including DNA replication, transcription and maintenance of genome stability. Here, we showed that Yin Yang-1 (YY1) can bind directly to G4 structures. ChIP-Seq results revealed that YY1 binding sites overlap extensively with G4 structure loci in chromatin. We also observed that YY1’s dimerization and its binding with G4 structures contribute to YY1-mediated long-range DNA looping. Displacement of YY1 from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 42 publications
(69 reference statements)
4
94
1
Order By: Relevance
“…According to the proposed model, YY1 forms homodimers, which can bring the associated gene enhancers and promoters closer together. A cluster of C2H2 domains and an adjacent unstructured domain are responsible for the dimerization and oligomerization of YY1 [ 103 , 104 ]. Moreover, the dimerization and subsequent oligomerization of YY1 results in non-specific binding to DNA, especially with guanine quadruplexes (G4).…”
Section: Mechanisms Of Distance Interaction Between Enhancers and mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the proposed model, YY1 forms homodimers, which can bring the associated gene enhancers and promoters closer together. A cluster of C2H2 domains and an adjacent unstructured domain are responsible for the dimerization and oligomerization of YY1 [ 103 , 104 ]. Moreover, the dimerization and subsequent oligomerization of YY1 results in non-specific binding to DNA, especially with guanine quadruplexes (G4).…”
Section: Mechanisms Of Distance Interaction Between Enhancers and mentioning
confidence: 99%
“…Moreover, the dimerization and subsequent oligomerization of YY1 results in non-specific binding to DNA, especially with guanine quadruplexes (G4). Some experimental evidence has suggested that the dimerization of YY1 and the subsequent binding to G4 structures contribute to the YY1-mediated formation of long DNA loops [ 104 ]. YY1 may also participate in the organization of distance interactions through the regulation of proteins that are directly involved in the formation of chromatin loops.…”
Section: Mechanisms Of Distance Interaction Between Enhancers and mentioning
confidence: 99%
“…According to the proposed model, YY1 forms homodimers, which can bring the associated gene enhancers and promoters closer together. A cluster of C2H2 domains and an adjacent unstructured domain are responsible for the dimerization and oligomerization of YY1 [90,91]. Moreover, the dimerization and subsequent oligomerization of YY1 results in non-specific binding to DNA, especially with guanine quadruplexes (G4).…”
Section: Distance Interaction Mechanisms Between Enhancers and Promotmentioning
confidence: 99%
“…Moreover, the dimerization and subsequent oligomerization of YY1 results in non-specific binding to DNA, especially with guanine quadruplexes (G4). Some experimental evidence has suggested that the dimerization of YY1 and the subsequent binding to G4 structures contribute to the YY1-mediated formation of long DNA loops [91]. YY1 may also participate in the organization of distance interactions through the regulation of proteins that are directly involved in the formation of chromatin loops.…”
Section: Distance Interaction Mechanisms Between Enhancers and Promotmentioning
confidence: 99%
“…In this regard, accumulating evidence suggests that, at accessible chromatin regions, 10 DNA folding into non-canonical structures may drive the recruitment of architectural proteins to promote gene clustering. 11,12 Among all DNA non-canonical secondary structures, G-quadruplexes (G4s) are tetra-helical arrangements that form within guanine-rich tracts. Here, four guanines interact through Hoogsteen hydrogen bonds to form planar arrays (G-tetrads) that stack one upon the other, building the core of the structure.…”
Section: Introductionmentioning
confidence: 99%